Brief Report: Effect of Antiretroviral Switch From Tenofovir Disoproxil fumarate to Tenofovir Alafenamide on Alanine Aminotransferase, Lipid Profiles, and Renal Function in HIV/HBV-Coinfected Individuals in a Nationwide Canadian Study. (1st December 2022) - Sarowar, Arif; Coffin, Carla S.; Fung, Scott; Wong, Alexander; Doucette, Karen; Truong, David; Conway, Brian; Haylock-Jacobs, Sarah; Ramji, Alnoor; Hansen, Bettina E.; Janssen, Harry L. A.; Cooper, Curtis
Abstract : Objective: Tenofovir alafenamide (TAF) achieves increased renal safety and improved alanine aminotransferase (ALT) normalization but increased lipid profile in hepatitis B virus (HBV)–monoinfected patients switched from tenofovir disoproxil fumarate (TDF). It is unclear whether HIV coinfection perturbs these biochemical changes. To this end, we assessed these parameters in HIV/HBV-coinfected patients switched from TDF to TAF. Design: Retrospective, multicenter, observational study. Methods: HIV/HBV-coinfected patients switched from TDF to TAF-based antiretroviral therapy (ART) at 6 Canadian Hepatitis B Network (CanHepB) academic sites were included. Changes in lipid profile, estimated glomerular filtration rate (eGFR), and ALT were evaluated using linear mixed effect model regression. Results: Eighty-two HIV/HBV-coinfected patients with a mean 103-week follow-up duration were identified. At time of TAF switch, 80 of 82 (98%) were HBV virally suppressed, 29 of 82 (35%) had elevated ALT levels, and 63 of 82 (77%) had eGFR of ≥60 mL/min per 1.73 m 2 . Twenty-six/Eighty-two (32%) had preexisting renal comorbidities. There were no changes in total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglyceride levels 2 years after TAF switch. Those with elevated ALT levels achieved greater ALT normalization after TAF switch (−0.004 [−0.008 to 0.0] log10 U/L/mo, P = 0.03). eGFR decline rate while on TDF (−0.66 [−0.23 to −1.08] mL/min/month, P < 0.005) was diminished after switching to TAF (−0.02 [−0.16 to 0.11] mL/min/mo, P = 0.7) and those with eGFR of <60 mL/min experienced increase in eGFR after TAF switch (0.45 [0.03–0.87] mL/min/mo, P = 0.04). Conclusions: Our study supports switching from TDF to TAF with positive influence on overall long-term biochemical profile in HIV/HBV-coinfected individuals.